Arabic Language Acquisition through Instagram Content Lughoty: Psycholinguistic Studies - Adira, Wafa Rizqiyya; Setiyawan, Agung; Ramadhan, Ahmad Rizki; Amaliah, Fildzah; Azzahra, Angelia Fathimah (UIN Sunan Gunung Djati Bandung, 2024)
This study was conducted based on the gap in student language environment while boarding and at home. Students can't feel the language environment at home, and there aren't digital learning media that can support the consistency of students' Arabic language acquisition. So, this research was carried out to make Instagram a place for students to acquire a second language and to determine the factors that can affect students' language acquisition based on psycholinguistic studies. This research uses descriptive qualitative methods, with data collection instruments in the form of unstructured interviews and description tests. The research sample was 20 SMAS La Tansa Islamic Boarding School students through a purposive sampling technique. Based on the test results, students could mention six new vocabulary words, one uslūb, and two words with writing errors. In addition, students can produce new sentences in Arabic through inference activities or reveal the implied meaning in the content. The language acquisition factors experienced by students are intrinsic in the form of interest, motivation, and language cognitive abilities. In contrast, extrinsic influences for students come from the language environment and curriculum design. The implication of this research for boarding school institutions is to integrate traditional curriculum and technology through Arabic language acquisition through instagram content so that Arabic language acquisition gives an interactive and up-to-date impression. Future research should explore its impact on language skills, compare it with other platforms, and study teachers' preparedness for digital integration.